The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.plaphy.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Cold stress affects H + -ATPase and phospholipase D activity in Arabidopsis

Abstract: a b s t r a c tLow temperature is an environmental stress that greatly influences plant performance and distribution. Plants exposed to cold stress exhibit modifications of plasma membrane physical properties that can affect their functionality. Here it is reported the effect of low temperature exposure of Arabidopsis plants on the activity of phospholipase D and H þ -ATPase, the master enzyme located at the plasma membrane.The H þ -ATPase activity was differently affected, depending on the length of cold stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 57 publications
1
30
1
Order By: Relevance
“…4). This suggested that ATP hydrolysis in RIL82 plants were adversely inhibited by cold stress, and thus the lower GSH synthesis because of the higher unavailable ATP (Puhakainen et al 1999;Mendoza et al 2000;Deng et al 2015;Muzi et al 2016). This hypothesis was confirmed by the present results that the PARP inhibitor (3-ab) only enhanced the cold tolerance and GSH content in ZZ39 plants under cold stress ( Fig.…”
Section: The Role Of Atp Hydrolysis In Gsh Synthesis In Rice Plants Usupporting
confidence: 84%
“…4). This suggested that ATP hydrolysis in RIL82 plants were adversely inhibited by cold stress, and thus the lower GSH synthesis because of the higher unavailable ATP (Puhakainen et al 1999;Mendoza et al 2000;Deng et al 2015;Muzi et al 2016). This hypothesis was confirmed by the present results that the PARP inhibitor (3-ab) only enhanced the cold tolerance and GSH content in ZZ39 plants under cold stress ( Fig.…”
Section: The Role Of Atp Hydrolysis In Gsh Synthesis In Rice Plants Usupporting
confidence: 84%
“…() as well as Muzi et al . () for examples) and not at the restrictive, low temperatures that we note can affect ATP synthase function.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, when plants are returned to higher, more moderate temperatures, ATP synthases or hydrolysis is enhanced. This phenomenon may explain why some studies report significant increases in ATP synthase or ATP lyase activity in the cold, as such experiments only involved measurements of the enzyme at 25°C or above (see Schulze et al (2012) as well as Muzi et al (2016) for examples) and not at the restrictive, low temperatures that we note can affect ATP synthase function.…”
Section: Researchmentioning
confidence: 96%
“…Moreover, PLD-derived PA may activate proton-pumps, like vacuolar H + -ATPase and H + -PPase, which confer a proton gradient for the Na + /H + exchange to enhance salt tolerance (Zhang et al, 2006; Shen et al, 2011). A new study also suggested that there was a functional correlation between the activities of PLD and the H + -ATPase mediated by PA release (Muzi et al, 2016). In this study, we monitor the expression levels of genes related to ion exchange, including NtNHX1 , NtNKT1 and NtHAK1 , and genes related to H + -ATPase, such as NtNHA1 and NtVAG1 , under short-term NaCl stress.…”
Section: Discussionmentioning
confidence: 99%